Pengaruh Rasio Keuangan Terhadap Kinerja Keuangan Pada Pt. Bank Negara Indonesia Tbk Periode 2013-2020 - Caecilia Rosma Widyohening; Luluk Maghfiroh (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2022)
Good financial performance is the main goal to be achieved by a company. This study discusses the effect of financial ratios on financial performance at PT. Bank Negara Indonesia Tbk Period 2013-2020. The purpose of this research is to find out how the effect of Capital Adequecy Ratio (CAR) on Retum On Asset (ROA), the effect of Non Performing Loan (NPL) on Retum On Asset (ROA), and the effect of Biaya Operasional Pendapatan Oprasional (BOPO) on Retum On Asset (ROA) at PT. Bank Negara Indonesia Tbk Period 2013-2020. This research is a type of quantitative research and data collection techinques, namely documentation by looking at financial reports which are accessed through the offical website of the IDX www.idx.co.id and using multiple linear regression analysis techniques. The results of the study which were processed with SPSS 22 based on the Persian Test (T) showed that the value of the Capital Adequecy Ratio (CAR) was 0.362 > 0.05, which means that NPL has on effecton Retum On Asset (ROA) and the value of Non Performing Loan (NPL) is 0.744 > 0.05 means that NPL has on effecton Retum On Asset (ROA) while showing the value of Biaya Operasional Pendapatan Oprasional (BOPO) of 0.036 < 0.05, which means that BOPO has a negative effect on Retum On Asset (ROA).